Trusted cloud broker for estimating the reputation of cloud providers in federated cloud environment. (28th July 2021) - Muralidharan, C.; Anitha, R.
Abstract: In federated cloud environment, it is too hard for the consumers to manage the services as multiple services may be rendered from multiple providers. Finding the trustable cloud service provider is an important and tedious process for the consumers before acquiring the services. In this proposed work, the reputation of the service providers are calculated through two different scenarios such as reputation estimation through consumer ratings and reputation estimation based on the trusted cloud broker (TCB) monitored data. The technical parameters such as availability of service, response time, bandwidth, throughput, and so forth, and nontechnical parameters such as service compliance, ease of access, support, readability of document, and so forth, of the rendered services are considered for analysis. The proposed model follows the fuzzy analytical hierarchical process principles that are used for ranking the services based on the quality of service and quality of experience metrics. The total reputations of the providers are calculated by combining the updated consumer reputation and the TCB estimated reputation. The performance of the proposed model is compared with the existing models such as RTM and CSTEM and found that the proposed model estimates the reputation with more accuracy.